Agronomic and economic performance of legume-legume and cereal-legume intercropping systems in Northern Tanzania - Kinyua, M.; Kihara, Job Maguta; Bekunda, Mateete A.; Bolo, Peter Omondi; Mairura, Franklin S.; Fischer, Gundula; Mucheru-Muna, M. (Elsevier, 2023)
CONTEXT Cereal-legume intercropping, a common practice among farmers in sub-Saharan Africa (SSA), is important for crop diversification, soil fertility improvement, household nutrition and climate adaptation. However, cereals often outcompete the intercropped legumes for growth resources resulting in low legume yields.